Toward Evidence-Based Practice. Issue 3 (May 2023) - Rohan, Annie; Giurgescu, Carmen; Hayman, Laura L.; Pasha, Veronica C.
Abstract : Experts suggest how 6 research articles can be used in nursing practice.